Adapting to constructivist approaches to entrepreneurship education in the Chinese classroom. Issue 8 (2nd August 2020) - Bell, Robin
ABSTRACT: Encouragement by the Chinese government for education to move from an emphasis on passive learning, rote memorisation and mechanical training towards the development and delivery of education using active, student-centred education approaches has resulted in tensions and challenges, one of which is the reaction of students previously used to traditional passive transmission learning. To study the challenges that Chinese students face when undertaking a constructivist experience-based entrepreneurship course focused on process rather than content, eight groups of business students at a Chinese university were tasked with developing projects which would add value to the university's international community. The qualitative research identified four key themes: a lack of familiarity with the constructivist learning process; group work and group dynamics; the linkage of taught content to practical activities; and the reflective process of learning in constructivist education. The findings and suggested remedies as to how these challenges can be minimised are discussed.